Tinjauan Normatif atas Kekosongan Regulasi Teknis dan Lemahnya Budaya Hukum Pejabat Administratif - Ratrisari, Elizabeth Prima; Rajagukguk, Jemimah Puteri; Manalu, Veronica Enjelina (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The enforcement of decisions by the Administrative Court (PTUN) is essential for upholding the rule of law and protecting citizens from harmful administrative acts. However, its effectiveness is hindered by low compliance, lack of clear execution mechanisms, weak sanctions, and limited oversight. This study uses a normative legal approach and qualitative methods to analyze these challenges and identify solutions. Findings highlight the absence of technical regulations and a weak legal culture among officials as key issues. To improve enforcement, this study recommends clearer execution rules, expanded PTUN authority, stronger institutional oversight, and active presidential involvement through performance evaluations. Strengthening these aspects will enhance legal certainty and public trust in administrative justice.